Experimental Study on Beam-Column Connections of Concrete Encased Cold-formed Steel Beams to Concrete-filled Steel Tube Columns. Issue 1 (February 2021) - Mosheer, Khamail Abdul-Mahdi; Dawood, M B; Ghalib, M H
Abstract: Experimental testing was done to investigate the flexural behaviours of internal roof beam-column connections. Four specimens were studied under static loads, one of which was specified as a reference reinforced concrete beam-column connection with regular bars as a conventional reinforcement for beam and column. The other specimens featured cold-formed steel plates with the equivalent area to regular bars as reinforcement, with square steel tube cross-sections filled with concrete used for columns. The results showed an increase in load carrying capacity and toughness for the experimental specimens as compared with conventional reinforcement beam-column connection. The concrete prevented local buckling of the cold-formed steel sections and improved the flexural bending capacity.